(untitled) (Jurnal Bahasa, 2003)
This article aimed to analyse interruptions in the turn-taking system of speech among Malay children. The results of the study showed that children create interruptions to give and add information, to get their turns to speak and to offer sympathy. However, interruption is also used as a strategy to show disagreement and to create conflict. Thus, the pragmatics approach is established as a capable way of interpreting the meaning of utterances in the Malay children s conversation. The combination of both Relevance Theory and Schlobinskis conversation analysis framework has resulted in significant findings about utterance meaning and the communicative behavior of Malay children.